Influencia familiar en el rendimiento académico de estudiantes de grado sexto en el municipio de hatonuevo -la guajira (2021)
In the present work, it is determined from the perspective of the students, with the in order to observe the family impact on the academic performance of children and young people sixth grade of the educational institution Nuestra Señora Del Carmen. It is examined whether your Participation is meaningful, whether it is good or bad, and how they help the student. We use a quantitative technique to evaluate and estimate the degree of family participation at school and its impact on school performance in the current study. We work in descriptive research and empirical-analytical research